Development of cooperation in Belarus and formation of personnel potential of the Belarusian State University in the 1920s - Khodzin, Siarhei M. (Journal of the Belarusian State University. History, 2021)
The relevance of the problems of cooperative construction in the formation of Belarusian scientific schools is determined. The role of the Belarusian State University in the development of problems of cooperation in the 1920s is characterised. The activity of S. L. Pevsner as a representative of the economic thought of the 1920s is studied. In the perspective of «history through personality», the problems of the formation of the personnel potential of Belarusian State University are revealed. The relations between the management and the teaching staff of the university, the status and issues of material well-being of teachers invited to Belarusian State University are characterised. The conclusion is made about a significant personnel shortage and the presence of serious competition in the personnel sphere of university science in the 1920s with the development of higher education in the USSR.